KENYAMANAN TERMAL RUANG TERBUKA HIJAU DI KAMPUS UNSRAT BERDASARKAN PERSEPSI PENGUNJUNG - Prestin Babo; Fabiola B. Saroinsong; Josephus I. Kalangi (Universitas Sam Ratulangi, 2017)
ABSTRACT Comforts could be defined as psychological and physical comforts. Psychological comfort could be perchieved by safety, peace, and relaxant feeling that felt personaly and subjectively measurable. In the meanwhile, physical comfort could be measured objectively such as spatial, visual, auditorial, and thermal. Open spaces are public space that accessible either directly within limited or indirectly within undeterminate period of time. Open spaces could appear as roads, sidewalks, urban spaces such as townparks, forests, and other similar things. This manuscript discussed about thermal comfort that felt by human whose had activity on an urban green space (Ruang Terbuka Hijau or RTH) of The University of Sam Ratulangi. This research aimed to studying respondent perceptions on the point of thermal comfort on The University of Sam Ratulangi’s RTH. This research used purposive sampling to select the urban green spaces which frequently accesed, while respondents are randomly chosen. These following 11 RTH known to be accessed frequently, they are FMIPA, FAPERTA, FAPET, BANK BNI, FPIK, FATEK, FEB, FISIP, FH, FKM A, and FKM B. This research concluded the most comfortable RTH based on respondent perceptions is FKM B (100%); followed by FAPERTA (94.1%), FATEK (82.4%), FAPET (80%), FEB (69.2%), FPIK (65%), Bank BNI (63.6%), FH (53.8%), FMIPA (45.5%), FKM A (33.3%), dan di FISIP (26.3%). Keywords: Perception, Green open space, Campus UNSRAT.